Fundamental role of BMP15 in human ovarian folliculogenesis revealed by null and missense mutations associated with primary ovarian insufficiency. Issue 5 (6th February 2020) - Rossetti, Raffaella; Ferrari, Ilaria; Bestetti, Ilaria; Moleri, Silvia; Brancati, Francesco; Petrone, Luisa; Finelli, Palma; Persani, Luca
Abstract: Bone morphogenetic protein 15 (BMP15) encodes an oocyte factor with a relevant role for folliculogenesis as homodimer or cumulin heterodimer (BMP15‐GDF9). Heterozygous BMP15 variants in the precursor or mature peptide had been associated with primary ovarian insufficiency (POI), but the underlying mechanism remains elusive and a double dose of BMP15 was suggested to be required for adequate ovarian reserve. We uncovered two homozygous BMP15 null variants found in two girls with POI and primary amenorrhea. Both heterozygous mothers reported physiological menopause. We then performed western blot, immunofluorescence, and reporter assays to investigate how previously reported missense variants, p.Y235C and p.R329C, located in the precursor or mature domains of BMP15, may affect protein function. The p.R329C variant demonstrates an impaired colocalization with growth/differentiation factor 9 (GDF9) at confocal images and diminished activation of the SMAD pathways at western blot and reporter assays in COV434 follicular cell line. In conclusion, BMP15 null mutations cause POI only in the homozygous state, thus discarding the possibility that isolated BMP15 haploinsufficiency can cause evident ovarian defects. Alternatively, heterozygous BMP15 missense variants may affect ovarian function by interfering with cumulin activity. Our data definitely support the fundamental role of BMP15 in human ovarian folliculogenesis. Abstract : We describe two consanguineous families with null mutations of bone morphogenetic protein 15 (BMP15) gene that are associated with primary ovarian insufficiency (POI) and primary amenorrhea in homozygous females. The whole of clinical and in vitro data lead us to conclude that isolated BMP15 haploinsufficiency cannot cause evident defects in ovarian function. However, heterozygous BMP15 missense variants might affect cumulin function thus definitely supporting the fundamental role of BMP15 in human ovarian folliculogenesis.